KINERJA BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) DALAM PENCEGAHAN BENCANA BANJIR DI KECAMATAN RAMBAH KABUPATEN ROKAN HULU TAHUN 2022 - Pebriani, Selvi; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
In this research, there are several problematic phenomena that were raised in 2022 in the performance of the Rokan Hulu Regional Disaster Management Agency (BPBD) in preventing floods in Rambah District, namely first, the number of flood events in Rambah District has increased from 2021 - 2022, the number of houses and public facilities that experiences damage due to floods that are not resolved every year and there are complaints from the public regarding the slow response of the Rokan Hulu BPBD in preventing floods which causes floods to continue to occur every month. From the above phenomenon, the aim of this research is to determine the performance of the regional disaster management agency (BPBD) in preventing flood disasters in Rambah District, Rokan Hulu Regency in 2022 along with the inhibiting factors. This research is descriptive research with a qualitative approach. The types of data are primary data and secondary data, primary data is obtained directly from informants. Meanwhile, secondary data is data that supports or strengthens primary data. Data collection techniques were carried out by means of interviews and documentation. The results of this research indicate that the performance of the Rokan Hulu BPBD has not been optimal according to its duties and functions in preventing floods, especially in Rambah District, socialization programs and physical infrastructure development for preventing flooding in the community have not been implemented. There are inhibiting factors in the form of a lack of coordination between agencies, inadequate operational vehicles, limited budgets that do not match the initial submission in the Draft Work Plan (RENJA), and the existence of global climate change which is very drastic so that disaster prevention is difficult to implement. Keywords: Bureaucratic Performance, Regional Disaster Management Agency (BPBD), Flood Prevention.